BLEEDING ASSESSMENT TOOLS - Veličković, Sanja; Vučić, Miodrag; Lilić, Božidar (Acta medicae Medianae, 2024)
Bleeding Assessment Tools (BATs) are bleeding scoring systems used for screening and quantitative assessment of mild bleeding disorders. They consist of a standardized questionnaire and a scoring system that is used for the summation of the final score. In this review article, we have presented BATs that are applied in the area of hematology.The earlier BATs were designed to distinguish patients with von Willebrand disease (VWD) from healthy individuals. Later modifications of the original Vicenza-BAT were developed in order to improve its specificity, precision, and flexibility, as well as to shorten the administration time. The most significant of these modifications is the International Society on Thrombosis and Hemostasis Bleeding Assessment Tool (ISTH-BAT), which is also validated for use in patients affected by hemophilia and inherited platelet disorders. ISTH-BAT score of ≥ 6 in adult females, ≥ 4 in adult males, and ≥ 3 in children is considered abnormal.The WHO developed the first BAT for immune thrombocytopenia (ITP). However, more recently, the ITP International Working Group (IWG) designed the ITP-BAT. The IWG defines a severe or clinically relevant bleeding manifestation as an ITP-BAT SMOG index of S > 2 and/or M > 1 and/or O > 1. In 2016, a group of Chinese experts created a simple modification of the ITP-BAT, the ITP-2016. The values of the ITP-2016 Bleeding Score ≥ 5 indicate severe immune thrombocytopenia.In the primary healthcare setting BATs serve as a valuable screening tool for discovering patients with bleeding disorders, who require further hematologic investigation.
Keywords: scoring, von Willebrand disease, platelet disorders, hemophilia, immune thrombocytopenia